1985
DOI: 10.1111/j.1432-1033.1985.tb09111.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the preferred Mg(II)‐adenine‐nucleotide complex at the active site of ectonucleotidases in intact vascular cells using phosphorothioate analogues of ADP and ATP

Abstract: In the presence of Mg' + the ecto-(nucleoside diphosphatase) on intact vascular endothelial or smooth muscle cells in culture selectively catabolises the PS diastereoisomer of adenosine 5'-[~-thio]diphosphate, (PSI-ADP [aS], and the ecto-(nucleoside triphosphatase) selectively catabolises the PS isomer of adenosine 5'- [P-thio] [l]) have proved to be powerful tools with which to analyse the stereochemical course of phosphorylation of phosphohydrolase reactions. The presence of stereoselectivity towards one is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In both cases the ATP effect was dose dependent; in the absence of Mg2+ its effect occurred at a nucleotide concentration lower than in the presence of Mg'+: the half-maximal concentration of ATP shifted from 0.25 to 0.16 mM with 5 mM MgCl2 ( fig.2A). These data establish that MgATP2-is not the entity involved in [Ca2']i enhancement and consequently demonstrate that ATP hydrolysis is not required, this complex being the preferential substrate of ATPases and kinases [16]. [lo].…”
Section: Resultsmentioning
confidence: 85%
“…In both cases the ATP effect was dose dependent; in the absence of Mg2+ its effect occurred at a nucleotide concentration lower than in the presence of Mg'+: the half-maximal concentration of ATP shifted from 0.25 to 0.16 mM with 5 mM MgCl2 ( fig.2A). These data establish that MgATP2-is not the entity involved in [Ca2']i enhancement and consequently demonstrate that ATP hydrolysis is not required, this complex being the preferential substrate of ATPases and kinases [16]. [lo].…”
Section: Resultsmentioning
confidence: 85%
“…However, in PGT-~3cells the concentrationdependence curves for UTP4 indicate that the P 2r eceptors are also responsive to the tetrabasic form of UTP. Other studies have also shown that P2ñucleotide receptors can be activated by UTP 4 as well as ATP4 (Pearson and Cusack, 1985;Lustig et al, 1992).…”
Section: Discussionmentioning
confidence: 89%
“…This conclusion was based on the observation that most of the nonhydrolyzable ATP analogs are much less potent, on a molar basis, than ATP; thus, ectonucleotidase activity may be required for complete P2y-purinoceptor activa tion. Subsequent work by Pearson and Cusack [32], has demonstrated that the P2y-purinoceptorand ecto-ATPase have distinct characteristics regarding stereospecific re quirements for the ATP molecule, which led them to con clude that the two are separate molecules. For example the P2y-purinoceptor demonstrates the greatest stcreospecific requirement for the ribose moiety, while ectoATPase is selective for the phosphate chain and requires a nucleotide/Mg2+ complex for activation [27], These con siderations.…”
Section: Discussionmentioning
confidence: 99%